The use of bacteriophage-based edible coatings for the biocontrol of Salmonella in strawberries. (May 2022) - Sezer, Banu; Tayyarcan, Emine Kubra; Boyaci, Ismail Hakki
Abstract: The physicochemical quality and the effectiveness of antimicrobial activity against Salmonella and phage stability of dip-coated strawberries were investigated in this study by using bacteriophage cocktail with four different biopolymers for a period of 5 day at +4°Ϲ. The biopolymers used in this study were whey protein concentrate (WPC), carboxymethyl cellulose (CMC), chitosan (CH), and sodium alginate (SA). The phage cocktail was prepared using S. Enteritidis and S. Typhimurium obtained from the phages isolated from different environmental sources as host bacteria. Uncoated fruit was used as a control. The color, pH, and titratable acidity (TA) of strawberry samples and the stability and antimicrobial activity of bacteriophages during storage were also investigated. Amongst all the biopolymers, WPC coating showed the least escalation in pH and the least decrease in TA. During storage, 0.7 log-unit (PFU/g) reduction in WPC coating with the bacteriophage cocktail was observed. The highest antimicrobial effect was observed in WPC with a reduction of 3.1 log (CFU/g) after 5 days when the multiplicity of infection was 1000. In the light of the results, it was concluded that the phage loaded WPC coating had much better physicochemical and microbiological quality during refrigerated storage; therefore, it could be used effectively to extend the postharvest life of strawberries. Highlights: The effect of WPC, CMC, CH, and SA coating on bacteriophage stability in 4°С was demonstrated. The edible WPC coatings significantly improved the stability of phages in refrigerated storage. The phage + WPC coating demonstrate high antimicrobial activity compared to controls in strawberries. The phage + WPC coating produced significant reduction in Salmonella count than other coatings.